Rethinking the PDH Bypass and GABA Shunt as Thiamin-Deficiency Workarounds . Issue 2 (13th August 2019) - Joshi, Jaya; Folz, Jacob S.; Gregory, Jesse F.; McCarty, Donald R.; Fiehn, Oliver; Hanson, Andrew D.
Abstract : The PDH bypass and the GABA shunt serve to maintain mainline metabolic fluxes during episodes of organellar thiamin diphosphate deficiency.